Wpływ pandemii COVID-19 na wykonywanie kompetencji przez miejskich (powiatowych) rzeczników konsumentów - Żądło, Adrian (Studia Prawa Publicznego, 2023)
The article aims to discuss the competencies of municipal and county consumer ombudsmen and how they were exercised by both before and under the conditions of the Covid-19 pandemic. The text presents the majority of the results of a survey conducted between 18 February and 4 March 2021, which involved submitting 142 requests for public information consisting of seven questions about the impact of the Covid-19 pandemic on the activities of consumer ombudsmen and their offices. Based on the criterion of population, requests were sent via email to consumer ombudsmen operating in most Polish cities with over 22,000 inhabitants. Requests were standardized as far as possible to obtain an unadulterated response from the ombudsmen. The research material consists of responses to requests for public information. The article is divided into several parts. The first discusses the position, competencies of ombudsmen and the ways in which they perform the tasks entrusted to them, drawing on legal acts, legal doctrine and reports on their activities published by the OCCP on the basis of annual reports submitted by them. The second part presents the results of a study on the impact of the Covid-19 pandemic on the ombudsmen’s activities, particularly focusing on the ways in which they perform their tasks and the changes implemented by them. Finally, based on the considerations made and the results of the research, conclusions are drawn regarding the activities undertaken by consumer ombudsmen in response to the challenges posed by the Covid-19 pandemic, the frequency of choosing specific communication methods and channels used to deliver consumer advices, and the types of new activities undertaken as a result of the Covid-19 pandemic and its associated restrictions. An attempt is made to formulate de lege ferenda conclusions regarding the competence in question.